Signaling between intracellular Ca2+ stores and depletion-activated Ca2+ channels generates [Ca2+]i oscillations in T lymphocytes (The Rockefeller University Press, 1994)
Stimulation through the antigen receptor (TCR) of T lymphocytes triggers cytosolic calcium ([Ca2+]i) oscillations that are critically dependent on Ca2+ entry across the plasma membrane. We have investigated the roles of Ca2+ influx and depletion of intracellular Ca2+ stores in the oscillation mechanism, using single-cell Ca2+ imaging techniques and agents that deplete the stores. Thapsigargin (TG; 5-25 nM), cyclopiazonic acid (CPA; 5-20 microM), and tert- butylhydroquinone (tBHQ; 80-200 microM), inhibitors of endoplasmic reticulum Ca(2+)-ATPases, as well as the Ca2+ ionophore ionomycin (5-40 nM), elicit [Ca2+]i oscillations in human T cells. The oscillation frequency is approximately 5 mHz (for ATPase inhibitors) to approximately 10 mHz (for ionomycin) at 22-24 degrees C. The [Ca2+]i oscillations resemble those evoked by TCR ligation in terms of their shape, amplitude, and an absolute dependence on Ca2+ influx. Ca(2+)- ATPase inhibitors and ionomycin induce oscillations only within a narrow range of drug concentrations that are expected to cause partial depletion of intracellular stores. Ca(2+)-induced Ca2+ release does not appear to be significantly involved, as rapid removal of extracellular Ca2+ elicits the same rate of [Ca2+]i decline during the rising and falling phases of the oscillation cycle. Both transmembrane Ca2+ influx and the content of ionomycin-releasable Ca2+ pools fluctuate in oscillating cells. From these data, we propose a model in which [Ca2+]i oscillations in T cells result from the interaction between intracellular Ca2+ stores and depletion-activated Ca2+ channels in the plasma membrane.